RELATIONS BETWEEN GENERAL MOTOR SKILLS AND "BALL SLALOM" IN FEMALE STUDENTS OF THE IV GRADE OF PRIMARY SCHOOL - Dragan Martinović; Dragan Branković; Jelena Ilić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Continuous monitoring of the level of motor development is one of the primary goals of teaching physical education. Gaining diversified movement experience and developing coordination is of particular importance at early school age. This is why modern approaches to teaching physical education give emphasis to the application of elements of sports games from the earliest age. Handball is a sports game which can be applied from the earliest school age because it abounds with a variety of movement tasks and includes natural forms of movement (running, jumping, throwing, etc.). Therefore, there is a great need for specific motor tests in handball. Specific motor tests are of great value, especially if observed in comparison to general motor skills results: handball requires a specific level of physical aptitude at the same timeinfluencing its further development and sustainability with its versatile contents. The specific coordination test "ball slalom" is broadly applicable and important in the overview of individual skills and can contribute to early guidance and selection in handball. That is why we tested general motor skills on a sample of 60 female students in the IV primary school grade. The testing was based on a battery of tests with the aim to find the mutual relations between these skills and the specific coordination test of "ball slalom". The aim was to check the possibilities of including a school of handball in the regular physical education curriculum.